Trends in myopia prevalence among children and adolescents: a large-scale cross-sectional study in Shihezi, China - Xiaopeng Hu; Xianyan Yuan; Hua Li; Haoxuan Gong; Zhicong Fu; Yuting Xie; Liqun Wang; Dongsheng Rui (BMC Public Health)
Abstract Purpose The aim of this study was to understand the trends of myopia prevalence among children and adolescents in Shihezi, China. Methods This was a cross-sectional study using data from 2018 to 2023 from the Vision Surveillance Research Program for Students in Shihezi City. Describe the prevalence of myopia with 95% CIs in 31,265 children and adolescents in urban and rural areas, by sex and age. The prevalence rate and chain growth rate of myopia and spherical equivalent refraction in different ages were described the development of myopia. Results A total of 31,265 children and adolescents with a mean age of 11,91 ± 3.67 years were included in the study. The overall prevalence of myopia was 50.93%(15924/31265, 95% CI: 50.38 − 51.49%). The prevalence of myopia was 55.18% (8348/15128, 95% CI: 54.39 − 55.98%) for girls and 46.95% (7576/16137, 95% CI: 46.18 − 47.72%) for boys. Prevalence of overall, mild, moderate, and high myopia is higher in urban than in rural areas. The prevalence of myopia increases with age, with the highest chain growth rate of myopia of 69.18% at the age of 6 years, slowing down at the age of 12 years. Spherical equivalent refraction changes from positive to negative at 6–7 years of age. Conclusions The prevalence of myopia is higher in Shihezi, and myopia develops at an earlier age and the farsighted disappears earlier. The development of myopia begins to increase sharply at the age of 6 years and slows down by the age of 12 years, and the spherical equivalent refraction changes from positive to negative at the age of 6 to 7 years. For policy makers, it is even more important to prevent and control myopia at a younger age.